Prácticas experimentales de laboratorio para el fortalecimiento del aprendizaje, en el bloque curricular de leyes del movimiento, del primer año de bachillerato general unificado paralelo A de la unidad educativa anexa a la Universidad Nacional De Loja. Periodo 2013-2014 - Herrera Yanangómez, Diego Vicente (2015)
The research was aimed to use of Experimental laboratory practices for strengthening of learning, in the curriculum block of motion laws, of the first year of unified general baccalaureate. The objective of the research process was proposed of as follows, use experimental laboratory practices for strengthen learning, in the curriculum block of motion laws. The research responded to a descriptive design (diagnosis) and Pre experimental. The phases used in its order were the follows: comprehensive, performed through by obtaining bibliographic data; diagnosis, to determine the difficulties, shortcomings and needs presented by students in learning the laws of motion; application models or experimental laboratory practices and the valuation model of effectiveness: Prueba Signo Rango de Wilcoxon. These allowed to demonstrate and reduce or mitigate the difficulties, shortcomings and needs present in the learning of the curriculum block of motion laws, by applying of experimental laboratory practices. The research showed that students have difficulty in interpreting the laws of motion and his relation to natural phenomena that occur in everyday life, moreover, that the use of experimental laboratory practices allows developing in students the ability to create your own knowledge through experimentation, facilitating learning of the laws of motion.